Freedom for the pike is death for the minnow – On the semantics of the Polish adverb dowolnie - Duraj-Nowosielska, Izabela (Papers in Linguistics, 2024)
Based on the assumptions of compositional semantics and using methods of structural description, the study presents a semantic analysis of the Polish word dowolnie [freely, randomly], partly in comparison with the adjective dowolny [free, random] and in polemics with other approaches to the word (including dictionary ones). Three meanings are distinguished – one metapredicative and two adverbial ones, with the current analysis focusing mainly on the latter, i.e. ad-verbum expressions. One of them comes close to the meaning of the pronoun jakkolwiek [in any way], and indicates the presence of various possibilities of action open to the subject; therefore, it assumes a non-factive sentential context, although in some cases an in-depth semantic interpretation is needed to recognise it. The metapredicative meaning is analogical, yet dowolnie does not refer here to the action of the subject, but to the activity of the speaker themselves, which is why it loses its relation to the verb at the object-level. The other type of adverbial use is based on factive contexts and communicates negative assessment of what the subject did; the point is that the agent, having had possibilities of action open, ultimately chose an option which, from the speaker’s perspective, is not sufficiently justified. This carries with itself a value of arbitrariness and incomprehensibility of the action from the speaker’s point of view, as evidenced by, among others, substitutability with the word arbitralnie [arbitrarily] and non-substitutability with jakkolwiek. The study also discusses the mechanism of perspective-switch underlying the distinction of these two variants as well as the linguistic status of all the three expressions.